Nuevos registros de aves para el Parque Provincial Aconcagua y zonas aledañas, Argentina - Ferrer, Diego; Escudero, Romina; Traslaviña, Alejandro; Navarro, Ezequiel (Nuestras Aves, 2013)
Este artículo no cuenta con un resumen.